Printing ink silk-screen anti-scratching method for LCD bottom polaroid
By replacing the polarizer with a special protective film, the problem of easy scratching of ink screen printing on LCD display screens is solved, reducing cost and thickness, and improving the mechanical and aging resistance of the product, achieving effective protection of the ink screen printing layer.
Patent Information
- Application Number
- CN202411412395.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-27
AI Technical Summary
When the existing LCD display is displayed in color, ink screen printed on the polarizer is easily scratched, affecting the display effect.
A special protective film is used instead of the polarizer, and the nano-reinforced powder and resin additional components are mixed to form a film with a thickness of 0.25mm to protect the ink screen printing layer and reduce the risk of scratching.
It reduces the cost of materials, reduces the total thickness of LCD, and effectively prevents scratches of the ink screen printing layer, improving the mechanical properties and aging resistance of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ink silk screen printing, and in particular to an anti-scratch method for ink silk screen printing on a bottom polarizer of an LCD. Background Art
[0002] Negative LCD displays on the market, especially VA (Vertical alignment) displays, need to screen-print the corresponding color ink on the display characters when color display is required. If the ink is screen-printed between the LCD glass and the polarizer, after turning on the backlight, you can see obvious screen-printed color blocks. The usual practice in the industry is to screen-print the ink on the bottom polarizer, which makes the screen-printed color blocks look less obvious and has a better display effect, but the ink exposed on the outer surface of the polarizer is easily scratched. Summary of the invention
[0003] To this end, the present invention provides a method for preventing scratches by silk-screen printing ink on a bottom polarizer of an LCD. After the polarizer is attached to the LCD screen, the ink is silk-screen printed on the bottom polarizer. After the ink is dried, a special protective film is attached and the protective film is defoamed. The preparation method of the special protective film is as follows: (1) preparing an ethanol solution of cerium nitrate, wherein the ethanol solution of cerium nitrate is kept at a constant temperature of 55±3° C. in a water bath, and the solution is stirred after being kept warm. Tetraethyl orthosilicate is added to the solution under stirring. After the addition is completed, the solution is kept warm at 55±3° C. and stirred for more than 30 minutes. Then the solution is transferred into a reaction kettle, the reaction kettle is sealed, heated to 120° C. and kept warm for 8 to 10 hours, and then air-cooled to room temperature, the reaction kettle is opened, the solution is spread in the container, the ethanol is dried in an oven to evaporate, and then calcined at 400 to 420° C. for 2 to 3 hours to obtain a nano-enhanced powder; (2) preparing an aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid; dispersing the nano-enhanced powder in an aqueous solution of ethanol to form a suspension, keeping the suspension constant temperature at 60±2° C. in a water bath, and then stirring the suspension while keeping the temperature constant. During the stirring process, adding the aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid to the suspension, stirring the suspension at a constant temperature of 60±2° C. for more than 20 minutes after the addition is completed, and then adding sodium hydroxide solution to the suspension to adjust the pH of the suspension to 10, and then continuing to stir the suspension at a constant temperature of 60±2° C. for more than 10 hours. After the stirring is completed, air cooling to room temperature is performed, solid-liquid separation is performed, and the solid phase is washed with ethanol and deionized water for more than 2 times each, and dried at 60° C. for more than 5 hours to obtain a modified powder; (3) In a nitrogen atmosphere, ABS high-rubber powder and maleic acid are mixed in toluene, the mixture is kept at a constant temperature of 82±2°C in a water bath under nitrogen protection for 20 minutes, and then the mixture is stirred. Benzoyl peroxide is added to the mixture under stirring. After the addition is completed, the mixture is kept at a constant temperature of 82±2°C under nitrogen protection for 5-6 hours. Then, anhydrous ethanol is added to the mixture for precipitation, the ethanol is filtered to remove, and then the mixture is washed with ethanol for more than 3 times and dried to obtain a resin additional component; (4) The modified powder, the resin additional component and the PET resin pellets are uniformly mixed to form a mixture, the mixture is melt-blended in an extruder at 240-270° C., extruded into pellets, injection molded into sheets, and statically biaxially stretched to a thickness of 0.25 mm to obtain the special protective film.
[0004] Furthermore, in the step (1), the concentration of cerium nitrate in the ethanol solution of cerium nitrate is 15-20 g / L, and the solvent is ethanol; the amount of tetraethyl orthosilicate added to the solution is tetraethyl orthosilicate: solution = 22-24 g: 1 L.
[0005] Furthermore, in the step (2), the concentration of N-trimethoxysilylpropylethylenediaminetriacetic acid sodium salt in the aqueous solution is 12-16 g / L, and the solvent is water; the nano-enhanced powder is dispersed in the aqueous solution of ethanol to form a suspension in a solid-liquid mass ratio of nano-enhanced powder / ethanol aqueous solution = 1:80, and the volume percentage of ethanol in the ethanol aqueous solution is 60%; the volume ratio of the aqueous solution of N-trimethoxysilylpropylethylenediaminetriacetic acid sodium salt added to the suspension is suspension: aqueous solution of N-trimethoxysilylpropylethylenediaminetriacetic acid sodium salt = 10:3-5; the mass percentage of sodium hydroxide in the sodium hydroxide solution is 5%, and the solvent is water.
[0006] Furthermore, in the step (3), the mass ratio of ABS high-rubber powder and maleic acid in toluene is ABS high-rubber powder: maleic acid: toluene = 1:2-4:100; the mass ratio of the added benzoyl peroxide to the total mass of the mixture is benzoyl peroxide: mixture = 0.01-0.02:100.
[0007] Furthermore, in the step (4), the mixed mass ratio of the modified powder, the resin additional component and the PET resin pellets is modified powder: resin additional component: PET resin pellets = 3-5:10-13:100.
[0008] Furthermore, the melt blending temperature range is 240°C, 250°C, 255°C, 260°C, and 270°C, and the die temperature is 270°C.
[0009] The beneficial effects of the present invention are as follows: the present invention adopts a self-made special protective film to replace the polarizer covering mode in the prior art, thereby replacing the polarizer with higher cost. After the improvement, the material cost is reduced, and the product profit is increased; and the anti-scratch effect is also achieved. The thickness of the special protective film used is thinner than that of the polarizer, thereby reducing the total thickness of the LCD. DETAILED DESCRIPTION
[0010] The present invention will be further described below in conjunction with the embodiments. Example
[0011] A method for preventing scratches by silk-screen printing ink on a bottom polarizer of an LCD. After the polarizer is attached to the LCD screen, silk-screen printing ink is performed on the bottom polarizer. After the ink is dried, a special protective film is attached and the protective film is defoamed. The preparation method of the special protective film is as follows: (1) preparing an ethanol solution of cerium nitrate, wherein the concentration of cerium nitrate in the ethanol solution of cerium nitrate is 15 g / L and the solvent is ethanol; the ethanol solution of cerium nitrate is kept at a constant temperature of 55±3° C. in a water bath, and the solution is stirred after being kept warm. Tetraethyl orthosilicate is added to the solution under stirring, and the amount ratio of tetraethyl orthosilicate added to the solution is 22 g: 1 L; after the addition is completed, the solution is kept warm at 55±3° C. and stirred for 30 min, and then the solution is transferred to a reactor, the reactor is sealed, heated to 120° C. and kept warm for 8 h, and then air-cooled to room temperature, the reactor is opened, the solution is spread in the container, the ethanol is dried in an oven to evaporate, and then calcined at 400° C. for 2 h to obtain a nano-enhanced powder; (2) preparing an aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid; in the aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid, the concentration of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid is 12 g / L, and the solvent is water; dispersing the nano-enhanced powder in the aqueous solution of ethanol to form a suspension, wherein the solid-liquid mass ratio of the nano-enhanced powder to the aqueous solution of ethanol to form a suspension is nano-enhanced powder / ethanol aqueous solution = 1:80, and the volume percentage of ethanol in the aqueous solution of ethanol is 60%; the suspension is kept at a constant temperature of 60±2° C. in a water bath, and then the suspension is stirred while being kept warm, and during the stirring process, the N-trimethoxysilylpropylethylenediaminetriacetic acid is added to the suspension. The aqueous solution of sodium salt of ethylenediaminetriacetic acid is added to the suspension in a volume ratio of suspension: aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid = 10:3; after the addition is completed, the suspension is stirred at a constant temperature of 60±2°C for 20 minutes, and then a sodium hydroxide solution is added to the suspension to adjust the pH of the suspension to 10, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 5%, and the solvent is water; then the suspension is stirred at a constant temperature of 60±2°C for 10 hours, and after the stirring is completed, the suspension is air-cooled to room temperature, solid-liquid separation is performed, the solid phase is washed twice with ethanol and deionized water, and dried at 60°C for 5 hours to obtain a modified powder; (3) In a nitrogen atmosphere, ABS high-glue powder and maleic acid are mixed in toluene, and the mass ratio of ABS high-glue powder and maleic acid in toluene is ABS high-glue powder: maleic acid: toluene = 1:2:100; the mixture is kept constant temperature at 82±2°C in a water bath under nitrogen protection for 20 minutes, and then the mixture is stirred. Benzoyl peroxide is added to the mixture under stirring, and the ratio of the added mass of the benzoyl peroxide to the total mass of the mixture is benzoyl peroxide: mixture = 0.01:100; after the addition is completed, the mixture is kept constant temperature at 82±2°C under nitrogen protection for 5 hours, and then the mixture is added to anhydrous ethanol for precipitation, the ethanol is filtered to remove, and then washed with ethanol for 3 times, and dried to obtain a resin additional component; (4) The modified powder, the resin additional component and the PET resin pellets are uniformly mixed to form a mixture, wherein the mass ratio of the modified powder, the resin additional component and the PET resin pellets is modified powder: resin additional component: PET resin pellets = 3:10:100; the mixture is melt-blended in an extruder at 240-270° C., the melt-blending temperature range is 240° C., 250° C., 255° C., 260° C., 270° C., and the die temperature is 270° C.; extrusion granulation is performed, and the mixture is injection-molded into a sheet at 270° C., and static biaxial stretching is performed to 3 times the size to form a film with a thickness of 0.25 mm to obtain the special protective film. Example
[0012] A method for preventing scratches by silk-screen printing ink on a bottom polarizer of an LCD. After the polarizer is attached to the LCD screen, silk-screen printing ink is performed on the bottom polarizer. After the ink is dried, a special protective film is attached and the protective film is defoamed. The preparation method of the special protective film is as follows: (1) preparing an ethanol solution of cerium nitrate, wherein the concentration of cerium nitrate in the ethanol solution of cerium nitrate is 17 g / L, and the solvent is ethanol; the ethanol solution of cerium nitrate is kept at a constant temperature of 55±3° C. in a water bath, and the solution is stirred after being kept warm. Tetraethyl orthosilicate is added to the solution under stirring, and the amount ratio of tetraethyl orthosilicate added to the solution is 23 g:1 L; after the addition is completed, the solution is kept warm at 55±3° C. and stirred for 30 minutes, and then the solution is transferred to a reactor, the reactor is sealed, heated to 120° C. and kept warm for 8 hours, and then air-cooled to room temperature, the reactor is opened, the solution is spread in the container, the ethanol is dried in an oven to evaporate, and then calcined at 400° C. for 2 hours to obtain a nano-enhanced powder; (2) preparing an aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid; in the aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid, the concentration of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid is 14 g / L, and the solvent is water; dispersing the nano-enhanced powder in the aqueous solution of ethanol to form a suspension, wherein the solid-liquid mass ratio of the nano-enhanced powder to the aqueous solution of ethanol to form a suspension is nano-enhanced powder / ethanol aqueous solution = 1:80, and the volume percentage of ethanol in the aqueous solution of ethanol is 60%; the suspension is kept at a constant temperature of 60±2° C. in a water bath, and then the suspension is stirred while being kept warm, and during the stirring process, the N-trimethoxysilylpropylethylenediaminetriacetic acid is added to the suspension. The aqueous solution of sodium salt of ethylenediaminetriacetic acid is added to the suspension in a volume ratio of suspension: aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid = 10:4; after the addition is completed, the suspension is stirred at a constant temperature of 60±2°C for 20 minutes, and then a sodium hydroxide solution is added to the suspension to adjust the pH of the suspension to 10, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 5%, and the solvent is water; then the suspension is stirred at a constant temperature of 60±2°C for 10 hours, and after the stirring is completed, the suspension is air-cooled to room temperature, solid-liquid separation is performed, the solid phase is washed twice with ethanol and deionized water, and dried at 60°C for 5 hours to obtain a modified powder; (3) In a nitrogen atmosphere, ABS high-glue powder and maleic acid are mixed in toluene, and the mass ratio of ABS high-glue powder and maleic acid in toluene is ABS high-glue powder: maleic acid: toluene = 1:3:100; the mixture is kept constant temperature at 82±2°C in a water bath under nitrogen protection for 20 minutes, and then the mixture is stirred. Benzoyl peroxide is added to the mixture under stirring, and the mass ratio of the added benzoyl peroxide to the total mass of the mixture is benzoyl peroxide: mixture = 0.01:100; after the addition is completed, the mixture is kept constant temperature at 82±2°C under nitrogen protection for 5 hours, and then the mixture is added to anhydrous ethanol for precipitation, the ethanol is filtered to remove, and then washed with ethanol for 3 times, and dried to obtain a resin additional component; (4) The modified powder, the resin additional component and the PET resin pellets are uniformly mixed to form a mixture, wherein the mass ratio of the modified powder, the resin additional component and the PET resin pellets is modified powder: resin additional component: PET resin pellets = 4:11:100; the mixture is melt-blended in an extruder at 240-270° C., the melt-blending temperature range is 240° C., 250° C., 255° C., 260° C., 270° C., and the die temperature is 270° C.; extrusion granulation is performed, and the mixture is injection-molded into a sheet at 270° C., and static biaxial stretching is performed to 3 times the size to form a film with a thickness of 0.25 mm to obtain the special protective film. Example
[0013] A method for preventing scratches by silk-screen printing ink on a bottom polarizer of an LCD. After the polarizer is attached to the LCD screen, silk-screen printing ink is performed on the bottom polarizer. After the ink is dried, a special protective film is attached and the protective film is defoamed. The preparation method of the special protective film is as follows: (1) preparing an ethanol solution of cerium nitrate, wherein the concentration of cerium nitrate in the ethanol solution of cerium nitrate is 19 g / L and the solvent is ethanol; the ethanol solution of cerium nitrate is kept at a constant temperature of 55±3° C. in a water bath, and the solution is stirred after being kept warm. Tetraethyl orthosilicate is added to the solution under stirring, and the amount ratio of tetraethyl orthosilicate added to the solution is 23 g:1 L; after the addition is completed, the solution is kept warm at 55±3° C. and stirred for 30 min, and then the solution is transferred to a reactor, the reactor is sealed, heated to 120° C. and kept warm for 8 h, and then air-cooled to room temperature, the reactor is opened, the solution is spread in the container, the ethanol is dried in an oven to evaporate, and then calcined at 400° C. for 2 h to obtain a nano-enhanced powder; (2) preparing an aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid; in the aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid, the concentration of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid is 14 g / L, and the solvent is water; dispersing the nano-enhanced powder in the aqueous solution of ethanol to form a suspension, wherein the solid-liquid mass ratio of the nano-enhanced powder to the aqueous solution of ethanol to form a suspension is nano-enhanced powder / ethanol aqueous solution = 1:80, and the volume percentage of ethanol in the aqueous solution of ethanol is 60%; the suspension is kept at a constant temperature of 60±2° C. in a water bath, and then the suspension is stirred while being kept warm, and during the stirring process, the N-trimethoxysilylpropylethylenediaminetriacetic acid is added to the suspension. The aqueous solution of sodium salt of ethylenediaminetriacetic acid is added to the suspension in a volume ratio of suspension: aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid = 10:4; after the addition is completed, the suspension is stirred at a constant temperature of 60±2°C for 20 minutes, and then a sodium hydroxide solution is added to the suspension to adjust the pH of the suspension to 10, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 5%, and the solvent is water; then the suspension is stirred at a constant temperature of 60±2°C for 10 hours, and after the stirring is completed, the suspension is air-cooled to room temperature, solid-liquid separation is performed, the solid phase is washed twice with ethanol and deionized water, and dried at 60°C for 5 hours to obtain a modified powder; (3) In a nitrogen atmosphere, ABS high-glue powder and maleic acid are mixed in toluene, and the mass ratio of ABS high-glue powder and maleic acid in toluene is ABS high-glue powder: maleic acid: toluene = 1:3:100; the mixture is kept constant at 82±2°C in a water bath under nitrogen protection for 20 minutes, and then the mixture is stirred. Benzoyl peroxide is added to the mixture under stirring, and the mass ratio of the added benzoyl peroxide to the total mass of the mixture is benzoyl peroxide: mixture = 0.02:100; after the addition is completed, the mixture is kept constant at 82±2°C under nitrogen protection for 5 hours, and then the mixture is added to anhydrous ethanol for precipitation, the ethanol is filtered to remove, and then washed with ethanol for 3 times, and dried to obtain a resin additional component; (4) The modified powder, the resin additional component and the PET resin pellets are mixed uniformly to form a mixture, wherein the mass ratio of the modified powder, the resin additional component and the PET resin pellets is modified powder: resin additional component: PET resin pellets = 4:12:100; the mixture is melt-blended in an extruder at 240-270° C., the melt-blending temperature range is 240° C., 250° C., 255° C., 260° C., 270° C., and the die temperature is 270° C.; extrusion granulation is performed, and the mixture is injection-molded into a sheet at 270° C., and static biaxial stretching is performed to 3 times the size to form a film with a thickness of 0.25 mm to obtain the special protective film. Example
[0014] A method for preventing scratches by silk-screen printing ink on a bottom polarizer of an LCD. After the polarizer is attached to the LCD screen, silk-screen printing ink is performed on the bottom polarizer. After the ink is dried, a special protective film is attached and the protective film is defoamed. The preparation method of the special protective film is as follows: (1) preparing an ethanol solution of cerium nitrate, wherein the concentration of cerium nitrate in the ethanol solution of cerium nitrate is 20 g / L, and the solvent is ethanol; the ethanol solution of cerium nitrate is kept at a constant temperature of 55±3° C. in a water bath, and the solution is stirred after being kept warm. Tetraethyl orthosilicate is added to the solution under stirring, and the amount ratio of tetraethyl orthosilicate added to the solution is 24 g: 1 L; after the addition is completed, the solution is kept warm at 55±3° C. and stirred for 30 minutes, and then the solution is transferred to a reactor, the reactor is sealed, heated to 120° C. and kept warm for 8 hours, and then air-cooled to room temperature, the reactor is opened, the solution is spread in the container, the ethanol is dried in an oven to evaporate, and then calcined at 400° C. for 2 hours to obtain a nano-enhanced powder; (2) preparing an aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid; in the aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid, the concentration of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid is 16 g / L, and the solvent is water; dispersing the nano-enhanced powder in the aqueous solution of ethanol to form a suspension, wherein the solid-liquid mass ratio of the nano-enhanced powder to the aqueous solution of ethanol to form a suspension is nano-enhanced powder / ethanol aqueous solution = 1:80, and the volume percentage of ethanol in the aqueous solution of ethanol is 60%; the suspension is kept at a constant temperature of 60±2° C. in a water bath, and then the suspension is stirred while being kept warm, and during the stirring process, the N-trimethoxysilylpropylethylenediaminetriacetic acid is added to the suspension. The aqueous solution of sodium salt of ethylenediaminetriacetic acid is added to the suspension in a volume ratio of suspension: aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid = 10:5; after the addition is completed, the suspension is stirred at a constant temperature of 60±2°C for 20 minutes, and then a sodium hydroxide solution is added to the suspension to adjust the pH of the suspension to 10, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 5%, and the solvent is water; then the suspension is stirred at a constant temperature of 60±2°C for 10 hours, and after the stirring is completed, the suspension is air-cooled to room temperature, solid-liquid separation is performed, the solid phase is washed twice with ethanol and deionized water, and dried at 60°C for 5 hours to obtain a modified powder; (3) ABS high-glue powder and maleic acid are mixed in toluene in a nitrogen atmosphere, and the mass ratio of ABS high-glue powder and maleic acid in toluene is ABS high-glue powder: maleic acid: toluene = 1:4:100; the mixture is kept constant temperature at 82±2°C in a water bath under nitrogen protection for 20 minutes, and then the mixture is stirred. Benzoyl peroxide is added to the mixture under stirring, and the mass ratio of the added benzoyl peroxide to the total mass of the mixture is benzoyl peroxide: mixture = 0.02:100; after the addition is completed, the mixture is kept constant temperature at 82±2°C under nitrogen protection for 5 hours, and then the mixture is added to anhydrous ethanol for precipitation, the ethanol is filtered to remove, and then washed with ethanol for 3 times, and dried to obtain a resin additional component; (4) The modified powder, the resin additional component and the PET resin pellets are mixed uniformly to form a mixture, wherein the mass ratio of the modified powder, the resin additional component and the PET resin pellets is modified powder: resin additional component: PET resin pellets = 5:13:100; the mixture is melt-blended in an extruder at 240-270° C., the melt-blending temperature range is 240° C., 250° C., 255° C., 260° C., 270° C., and the die temperature is 270° C.; extrusion granulation is performed, and the mixture is injection-molded into a sheet at 270° C., and static biaxial stretching is performed to 3 times the size to form a film with a thickness of 0.25 mm to obtain the special protective film.
[0015] Comparative Example 1 A method for preparing a protective film as a comparison is: (1) ball-milling the cerium dioxide powder, passing it through a 2000-mesh sieve, and collecting the sieved powder as the nano-enhanced powder of this comparative example; (2) preparing an aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid; in the aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid, the concentration of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid is 14 g / L, and the solvent is water; dispersing the nano-enhanced powder in the aqueous solution of ethanol to form a suspension, wherein the solid-liquid mass ratio of the nano-enhanced powder to the aqueous solution of ethanol to form a suspension is nano-enhanced powder / ethanol aqueous solution = 1:80, and the volume percentage of ethanol in the aqueous solution of ethanol is 60%; the suspension is kept at a constant temperature of 60±2° C. in a water bath, and then the suspension is stirred while being kept warm, and during the stirring process, the N-trimethoxysilylpropylethylenediaminetriacetic acid is added to the suspension. The aqueous solution of sodium salt of ethylenediaminetriacetic acid is added to the suspension in a volume ratio of suspension: aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid = 10:4; after the addition is completed, the suspension is stirred at a constant temperature of 60±2°C for 20 minutes, and then a sodium hydroxide solution is added to the suspension to adjust the pH of the suspension to 10, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 5%, and the solvent is water; then the suspension is stirred at a constant temperature of 60±2°C for 10 hours, and after the stirring is completed, the suspension is air-cooled to room temperature, solid-liquid separation is performed, the solid phase is washed twice with ethanol and deionized water, and dried at 60°C for 5 hours to obtain a modified powder; (3) In a nitrogen atmosphere, ABS high-glue powder and maleic acid are mixed in toluene, and the mass ratio of ABS high-glue powder and maleic acid in toluene is ABS high-glue powder: maleic acid: toluene = 1:3:100; the mixture is kept constant at 82±2°C in a water bath under nitrogen protection for 20 minutes, and then the mixture is stirred. Benzoyl peroxide is added to the mixture under stirring, and the mass ratio of the added benzoyl peroxide to the total mass of the mixture is benzoyl peroxide: mixture = 0.02:100; after the addition is completed, the mixture is kept constant at 82±2°C under nitrogen protection for 5 hours, and then the mixture is added to anhydrous ethanol for precipitation, the ethanol is filtered to remove, and then washed with ethanol for 3 times, and dried to obtain a resin additional component; (4) The modified powder, the resin additional component and the PET resin pellets are mixed uniformly to form a mixture, wherein the mass ratio of the modified powder, the resin additional component and the PET resin pellets is modified powder: resin additional component: PET resin pellets = 4:12:100; the mixture is melt-blended in an extruder at 240-270° C., the melt-blending temperature range is 240° C., 250° C., 255° C., 260° C., 270° C., and the die temperature is 270° C.; extrusion granulation is performed, and the mixture is injection-molded into a sheet at 270° C., and static biaxial stretching is performed to 3 times the size to form a film with a thickness of 0.25 mm, thereby obtaining the protective film for comparison.
[0016] Comparative Example 2 A method for preparing a protective film as a comparison is: (1) preparing an ethanol solution of cerium nitrate, wherein the concentration of cerium nitrate in the ethanol solution of cerium nitrate is 19 g / L and the solvent is ethanol; the ethanol solution of cerium nitrate is kept at a constant temperature of 55±3° C. in a water bath, and the solution is stirred after being kept warm. Tetraethyl orthosilicate is added to the solution under stirring, and the amount ratio of tetraethyl orthosilicate added to the solution is 23 g:1 L; after the addition is completed, the solution is kept warm at 55±3° C. and stirred for 30 min, and then the solution is transferred to a reactor, the reactor is sealed, heated to 120° C. and kept warm for 8 h, and then air-cooled to room temperature, the reactor is opened, the solution is spread in the container, the ethanol is dried in an oven to evaporate, and then calcined at 400° C. for 2 h to obtain a nano-enhanced powder; (2) ABS high-glue powder and maleic acid are mixed in toluene in a nitrogen atmosphere, and the mass ratio of ABS high-glue powder and maleic acid in toluene is ABS high-glue powder: maleic acid: toluene = 1:3:100; the mixture is kept constant temperature at 82±2°C in a water bath under nitrogen protection for 20 minutes, and then the mixture is stirred. Benzoyl peroxide is added to the mixture under stirring, and the mass ratio of the added benzoyl peroxide to the total mass of the mixture is benzoyl peroxide: mixture = 0.02:100; after the addition is completed, the mixture is kept constant temperature at 82±2°C under nitrogen protection for 5 hours, and then the mixture is added to anhydrous ethanol for precipitation, the ethanol is filtered to remove, and then washed with ethanol for 3 times, and dried to obtain a resin additional component; (3) The nano-reinforced powder, the resin additional component and the PET resin pellets are mixed uniformly to form a mixture, wherein the mass ratio of the nano-reinforced powder, the resin additional component and the PET resin pellets is nano-reinforced powder: resin additional component: PET resin pellets = 4:12:100; the mixture is melt-blended in an extruder at 240-270°C, the melt-blending temperature range is 240°C, 250°C, 255°C, 260°C, 270°C, and the die temperature is 270°C; extrusion granulation is performed, and the mixture is injection-molded into a sheet at 270°C, and static biaxial stretching is performed to 3 times the size to form a film with a thickness of 0.25 mm to obtain the protective film for comparison.
[0017] Comparative Example 3 A method for preparing a protective film as a comparison is: (1) preparing an ethanol solution of cerium nitrate, wherein the concentration of cerium nitrate in the ethanol solution of cerium nitrate is 19 g / L and the solvent is ethanol; the ethanol solution of cerium nitrate is kept at a constant temperature of 55±3° C. in a water bath, and the solution is stirred after being kept warm. Tetraethyl orthosilicate is added to the solution under stirring, and the amount ratio of tetraethyl orthosilicate added to the solution is 23 g:1 L; after the addition is completed, the solution is kept warm at 55±3° C. and stirred for 30 min, and then the solution is transferred to a reactor, the reactor is sealed, heated to 120° C. and kept warm for 8 h, and then air-cooled to room temperature, the reactor is opened, the solution is spread in the container, the ethanol is dried in an oven to evaporate, and then calcined at 400° C. for 2 h to obtain a nano-enhanced powder; (2) preparing an aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid; in the aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid, the concentration of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid is 14 g / L, and the solvent is water; dispersing the nano-enhanced powder in the aqueous solution of ethanol to form a suspension, wherein the solid-liquid mass ratio of the nano-enhanced powder to the aqueous solution of ethanol to form a suspension is nano-enhanced powder / ethanol aqueous solution = 1:80, and the volume percentage of ethanol in the aqueous solution of ethanol is 60%; the suspension is kept at a constant temperature of 60±2° C. in a water bath, and then the suspension is stirred while being kept warm, and during the stirring process, the N-trimethoxysilylpropylethylenediaminetriacetic acid is added to the suspension. The aqueous solution of sodium salt of ethylenediaminetriacetic acid is added to the suspension in a volume ratio of suspension: aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid = 10:4; after the addition is completed, the suspension is stirred at a constant temperature of 60±2°C for 20 minutes, and then a sodium hydroxide solution is added to the suspension to adjust the pH of the suspension to 10, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 5%, and the solvent is water; then the suspension is stirred at a constant temperature of 60±2°C for 10 hours, and after the stirring is completed, the suspension is air-cooled to room temperature, solid-liquid separation is performed, the solid phase is washed twice with ethanol and deionized water, and dried at 60°C for 5 hours to obtain a modified powder; (3) ABS high-rubber powder is used as the resin additional component of this comparative example; (4) The modified powder, the resin additional component and the PET resin pellets are mixed uniformly to form a mixture, wherein the mass ratio of the modified powder, the resin additional component and the PET resin pellets is modified powder: resin additional component: PET resin pellets = 4:12:100; the mixture is melt-blended in an extruder at 240-270° C., the melt-blending temperature range is 240° C., 250° C., 255° C., 260° C., 270° C., and the die temperature is 270° C.; extrusion granulation is performed, and the mixture is injection-molded into a sheet at 270° C., and static biaxial stretching is performed to 3 times the size to form a film with a thickness of 0.25 mm, thereby obtaining the protective film for comparison. Example
[0018] The tensile strength of the protective films prepared in the above embodiments and comparative examples was tested according to the requirements of the national standard GB / T 1040.3-2006, and the test speed was 50 mm / min. In addition, the aging resistance of the protective films prepared in the above embodiments and comparative examples was tested according to the requirements of the standard ISO 4892.3-2006. The lamp type was UVA-340 (type 1A), the test temperature was 70°C ± 3°C, and the irradiance was 0.83 W / (m 2 ·nm), turn off the light for 1 hour after 4 hours of illumination, and test for a total of 50 hours. After aging, the tensile strength after aging was tested according to the above method, and the strength retention rate was calculated. Strength retention rate = tensile strength after aging ÷ tensile strength before aging × 100%. The results are shown in Table 1.
[0019] Experimental Group Tensile strength(MPa) Aging strength retention rate (%) Example 1 114 71.5 Example 2 119 72.1 Example 3 122 72.8 Example 4 120 72.6 Comparative Example 1 107 68.4 Comparative Example 2 89 50.7 Comparative Example 3 93 55.3 As shown in Table 1, the special protective film prepared by the method of the present invention has good mechanical properties and aging resistance, can better protect the ink screen printing layer, reduce scratches, and improve the product qualification rate. This may be mainly because the addition of modified powder helps to play a second phase strengthening role in the PET resin matrix, thereby improving the strength of the special protective film. In addition, after the powder is modified and the resin additional components are added, on the one hand, the bonding force between the powder and the PET matrix is improved, the difficulty of crack generation and expansion is increased, and the powder is distributed more evenly in the matrix, avoiding the damage of the entire protective film caused by cracking due to low local strength.
[0020] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preventing scratches by silk-screen printing of ink on a bottom polarizer of an LCD, characterized in that: After the LCD screen is pasted with polarizer, ink is screen printed on the bottom polarizer. After the ink is dried, a special protective film is pasted and the protective film is defoamed. The preparation method of the special protective film is as follows: (1) preparing an ethanol solution of cerium nitrate, wherein the ethanol solution of cerium nitrate is kept at a constant temperature of 55±3° C. in a water bath, and the solution is stirred after being kept warm. Tetraethyl orthosilicate is added to the solution under stirring. After the addition is completed, the solution is kept warm at 55±3° C. and stirred for more than 30 minutes. Then the solution is transferred into a reaction kettle, the reaction kettle is sealed, heated to 120° C. and kept warm for 8 to 10 hours, and then air-cooled to room temperature, the reaction kettle is opened, the solution is spread in the container, the ethanol is dried in an oven to evaporate, and then calcined at 400 to 420° C. for 2 to 3 hours to obtain a nano-enhanced powder; (2) preparing an aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid; dispersing the nano-enhanced powder in an aqueous solution of ethanol to form a suspension, keeping the suspension constant temperature at 60±2° C. in a water bath, and then stirring the suspension while keeping the temperature constant. During the stirring process, adding the aqueous solution of sodium salt of N-trimethoxysilylpropylethylenediaminetriacetic acid to the suspension, stirring the suspension at a constant temperature of 60±2° C. for more than 20 minutes after the addition is completed, and then adding sodium hydroxide solution to the suspension to adjust the pH of the suspension to 10, and then continuing to stir the suspension at a constant temperature of 60±2° C. for more than 10 hours. After the stirring is completed, air cooling to room temperature is performed, solid-liquid separation is performed, and the solid phase is washed with ethanol and deionized water for more than 2 times each, and dried at 60° C. for more than 5 hours to obtain a modified powder; (3) In a nitrogen atmosphere, ABS high-rubber powder and maleic acid are mixed in toluene, the mixture is kept at a constant temperature of 82±2°C in a water bath under nitrogen protection for 20 minutes, and then the mixture is stirred. Benzoyl peroxide is added to the mixture under stirring. After the addition is completed, the mixture is kept at a constant temperature of 82±2°C under nitrogen protection for 5-6 hours. Then, anhydrous ethanol is added to the mixture for precipitation, the ethanol is filtered to remove, and then the mixture is washed with ethanol for more than 3 times and dried to obtain a resin additional component; (4) The modified powder, the resin additional component and the PET resin pellets are uniformly mixed to form a mixture, the mixture is melt-blended in an extruder at 240-270° C., extruded into pellets, injection molded into sheets, and statically biaxially stretched to a thickness of 0.25 mm to obtain the special protective film.
2. The method for preventing scratches by silk-screen printing of ink on the bottom polarizer of LCD according to claim 1, characterized in that: In the step (1), the concentration of cerium nitrate in the ethanol solution of cerium nitrate is 15-20 g / L, and the solvent is ethanol; the amount of tetraethyl orthosilicate added to the solution is tetraethyl orthosilicate: solution = 22-24 g: 1 L.
3. The method for preventing scratches by silk-screen printing of ink on a bottom polarizer of an LCD according to claim 1, characterized in that: In the step (2), the concentration of N-trimethoxysilylpropylethylenediaminetriacetic acid sodium salt in the aqueous solution is 12-16 g / L, and the solvent is water; the nano-enhanced powder is dispersed in the ethanol aqueous solution to form a suspension with a solid-liquid mass ratio of nano-enhanced powder / ethanol aqueous solution = 1:80, and the volume percentage of ethanol in the ethanol aqueous solution is 60%; the volume ratio of the aqueous solution of N-trimethoxysilylpropylethylenediaminetriacetic acid sodium salt added to the suspension is suspension: aqueous solution of N-trimethoxysilylpropylethylenediaminetriacetic acid sodium salt = 10:3-5; the mass percentage of sodium hydroxide in the sodium hydroxide solution is 5%, and the solvent is water.
4. The method for preventing scratches by silk-screen printing of ink on a bottom polarizer of an LCD according to claim 1, characterized in that: In the step (3), the mass ratio of ABS high-rubber powder and maleic acid in toluene is ABS high-rubber powder: maleic acid: toluene = 1:2-4:100; the mass ratio of the added benzoyl peroxide to the total mass of the mixture is benzoyl peroxide: mixture = 0.01-0.02:
100.
5. The method for preventing scratches by silk-screen printing of ink on a bottom polarizer of an LCD according to claim 1, characterized in that: In the step (4), the mixed mass ratio of the modified powder, the resin additional component and the PET resin pellets is modified powder: resin additional component: PET resin pellets = 3-5:10-13:
100.
6. The method for preventing scratches by silk-screen printing of ink on a bottom polarizer of an LCD according to claim 1, characterized in that: The melt blending temperature range is 240°C, 250°C, 255°C, 260°C, and 270°C, and the die temperature is 270°C.
